ANALISIS KEWAJIBAN PPH PASAL 21 PT. CDS PADA TAHUN PAJAK 2021 - Darell, Christopher; Widjaja, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The results of this study aim to identify PT. CDS’ compliance as taxpayer in fulfilling the calculating, paying, and reporting tax obligations in 2021. PT. CDS is engaged in manufacturing Garment Products to be supplied to several brands and offices. The results of this study indicate that PT. CDS has not fully carried out its calculation obligations in accordance with the applicable law, but has fully carried out its payments and reporting obligations in accordance with the regulations.